PENGARUH PELAYANAN KONSUMEN DI HOTEL SURYA KENCANA SURABAYA - Puji Astuti (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
Now a days tourism and hospitality industry especially in Hotel is growing fast, the writer take an observation as hotel X in Surabaya. The writer want to know influence of consument on education, level of service and policy as a leader on occupancy of Hotel X in front office Dept. front office one of central Dept in hotel as Relationship between guest and others Dept. Because of front office as central therefore front office will be brandage of image of the hotel . that’s why front office staff must have an experience and out standing skill because customer need good service expectation is priority. Hotel X in Surabaya can operates day to day operational well. It showed by result of hotel occupancy in stability over the everages. in case of this we conclude that good sevice is one of main factor will cause effect relationship of level about high of occupancy Hotel goes running well ,eventhough human resource minimizely. base in the above mater, impact of effect in the level on hotel occupancy in Surabaya because of good service to the guest.